Sodium dodecyl sulfate mediated microwave synthesis of biocompatible superparamagnetic mesoporous hydroxyapatite nanoparticles using black Chlamys varia seashell as a calcium source for biomedical applications. Issue 12 (15th August 2019) - Karunakaran, Gopalu; Cho, Eun-Bum; Kumar, Govindan Suresh; Kolesnikov, Evgeny; Karpenkov, Dmitriy Yu; Gopinathan, Janarthanan; Pillai, Mamatha Muraleedharan; Selvakumar, Rajendran; Boobalan, Selvakumar; Gorshenkov, Mikhail V.
Abstract: Designing biocompatible superparamagnetic mesoporous nanoparticles for advanced healthcare applications has received much attention. In this research, we have synthesized intrinsic mesoporous superparamagnetic hydroxyapatite (HAp) nanoparticles using bio-waste of black Chlamys varia seashell as a calcium source by sodium dodecyl sulfate (SDS)–enabled microwave-assisted synthesis approach. The synthesized Fe-doped HAp nanoparticles were characterized using various characterization techniques to know the phase purity and morphological features. The incorporation of Fe greatly affected the morphology of HAp nanoparticles without affecting their crystalline phase. Superparamagnetic behavior was observed with the incorporation of Fe in the HAp nanoparticles. Further, saturation magnetization was enhanced with higher incorporation of Fe ions. The cytotoxicity studies of the synthesized pure and Fe-doped HAp samples conducted using a human osteoblasts cell line (MG63), which indicated that Fe-doped HAp nanoparticles are biocompatible. Further, antibacterial activity analysis also confirmed their excellent antibacterial performance against different pathogens. Hence, SDS-enabled microwave-assisted synthesis approach using seashell as a calcium source would be a better approach for the production of intrinsic mesoporous superparamagnetic HAp nanoparticles for various biomedical applications, such as drug targeting, hyperthermia cancer therapy, and magnetic resonance imaging.